2005
DOI: 10.1007/s10802-005-5723-1
|View full text |Cite
|
Sign up to set email alerts
|

The Latent Structure of Psychopathy in Youth: A Taxometric Investigation

Abstract: Using taxometric procedures, the latent structure of psychopathy was investigated in two studies of children and adolescents. Prior studies have identified a taxon (i.e., a natural category) associated with antisocial behavior in adults as well as children and adolescents. However, features of this taxon suggest that it is not psychopathy but rather a broader class consistent with the construct of life course persistent antisocial behavior. Because the only prior study of youth used a non-clinical sample, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 71 publications
4
90
2
Order By: Relevance
“…Using a school-based sample of 1,111 boys (M age = 8 years), Skilling et al (2001) found taxonic results for DSM-IV CD. Vasey et al (2005) found similar results among a sample comprising 386 normal children, children referred for severe emotional/behavioral problems, and adolescents in a juvenile justice diversion program. One adult study (Skilling et al, 2002) conducted among 74 male inmates concluded that both DSM-IV ASPD and CD were taxonic.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Using a school-based sample of 1,111 boys (M age = 8 years), Skilling et al (2001) found taxonic results for DSM-IV CD. Vasey et al (2005) found similar results among a sample comprising 386 normal children, children referred for severe emotional/behavioral problems, and adolescents in a juvenile justice diversion program. One adult study (Skilling et al, 2002) conducted among 74 male inmates concluded that both DSM-IV ASPD and CD were taxonic.…”
supporting
confidence: 52%
“…First, very few taxometric studies were conducted in general population samples, and even fewer used assessment instruments explicitly designed to measure DSM criteria. Second, taxometric studies that found taxonic structures underlying CD and ASPD (Ayers 2000;Harris et al, 1994;Skilling et al, 2001Skilling et al, , 2002Vasey et al, 2005) relied on visual inspections of taxometric graphs and use of the Goodness of Fit Index (Waller and Meehl, 1998). These methods are less rigorous than the more recently developed comparison curve fi t index (CCFI; , which systematically compares the fi t of taxometric data to simulated taxonic and dimensional data.…”
mentioning
confidence: 99%
“…The frequency with which female adolescents were classifi ed into the clinical range of Delinquent Behavior and Aggressive Behavior was greater than that of male adolescents, a fi nding that differs from those reported in the literature (Nurmi, 1997;Vasey, Kotov, Frick, & Loney, 2005), though some studies have also found a relationship between the female gender and externalizing problems, often associated with depression (Silva, 2003;Honkalampi et al, 2009). Female adolescents are currently more assertive than male adolescents and many of their behaviors are alike, though girls judge themselves by a different standard.…”
Section: Discussioncontrasting
confidence: 63%
“…Schizotypy research often is biologically oriented due to its relation to schizophrenia, examining that disorder's full range of neurocognitive deficits; also, several studies have investigated the structure of self-reported dimensions of schizotypy. Focal assessment topics that deserve mention include gender bias, ethnicity/cultural issues, depressive PD (as a possible addition), taxometric analyses [somewhat supportive of schizotypal and antisocial PD categories; mixed, but more suggesting dimensional constructs for borderline personality disorder (BPD), narcissistic PD, and psychopathy; Edens et al 2006, Fossati et al 2005, Haslam 2003, Rothschild et al 2003, Vasey et al 2005, and the utility of brief screening instruments.…”
Section: Topics Not Reviewedmentioning
confidence: 99%